Corruption Prevention Management in Village Fund Management - Andi Irwan; Isma Fadilah; Nurul Husdayanti (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
Since the rollout of village funds in 2015 to 2018, around 186 trillion in village funds have flowed to 74,954 villages throughout Indonesia. And according to ICW, during this period, cases of corruption in village funds continued to increase from year to year and there were at least 181 cases of corruption recorded with a state loss of 40.6 billion. This fraud is not solely due to legal factors. But also because of administrative problems related to management, such as weak supervision in the management of village funds, management of village funds is not transparent and accountable, salaries and allowances for village officials are still low and other management problems that encourage village officials to commit corruption. Therefore, corruption prevention management is needed in the form of strengthening the supervisory function both institutionally and strengthening the position of the community as the party that can supervise the management of village funds. Apart from that, the recruitment pattern for Village Head Candidates must be improved, namely implementing strict requirements. Furthermore, the welfare of village officials must be improved through a mechanism for providing adequate wages and allowances according to the regional conditions of each village. Then, the village government is obliged to publish the management of village funds starting from planning to submitting reports (LPJ) on the use of village funds in order to create transparent and accountable village fund management. And finally, the central government needs to evaluate the impact of providing village funds on the welfare of village communities.